Pertumbuhan Jintan Hitam (Nigella sativa L.) pada Tingkat Naungan dan Pemupukan Nitrogen yang Berbeda - Setiawati, Evi; Kurniawati, Ani; Widodo, Winarso Drajad; Faridah, dan Didah Nur (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Black cumin (Nigella sativa L.) is an introduced medicinal plant therefore requires investigations to establish recommended cultivation procedure in tropical areas. Black cumin seeds contain a various bioactive compounds not only for culinary but also for medicinal purposes. This study was conducted to investigate the effect of nitrogen rates and shade levels on growth of Black cumin. The activity was carried out in Pasir Sarongge experimental station, Cianjur, West Java (1,117 masl). The research was arranged in nested design with three replications.  Nitrogen rates was nested within shading levels. The shading levels consist of 0%, 25%, 50%, and 75% which resulted in light intensity of 27,800, 17,400, 11,900, and 1,600 lux respectively. The Nitrogen rates consisted 0, 60, 120, and 180 kg ha-1. The results showed that shading up to 50% did not affect plant growth and did not reduce seed production. However, shading up to 75% prolong the vegetative period, decreased leaf thickness and plant dry weight. The higher the shading level up to 50%, the higher the plant height, leaf area, number of leaves and number of flower, but not number of branche. Nitrogen fertilizer 60 kg ha-1 increased number of blooming flower and number of capsule set.